Serviço social na educação: saberes e competências necessárias no fazer profissional - Souza, Iris de Lima (2008)
The Theory analyzes what should know and what competes, formally, to the Professional of Social Service to act in the School Education. He/she investigates, starting from studies on the theme, and close to Council Federal and Regional of Social Service, and of the Brazilian Association of Studies and Researches in Social Service, that you know and competences are necessary for the social worker performance in that specific area. Through a research of nature empiric, bibliographical and documental, the analysis focus outlines the glance and the understanding of the professionals' category that represent the defense organs, fiscalization and formation of the profession. The importance of the scientific study is justified for the social worker necessary contribution acting in the School Education, whose political and pedagogic context presents multiple demands, you know and relationships, and when it is lived a social and education picture at the present time with order words in formation, as inclusion, empowerment, competence, that they demand other specialists in the school scenery to work with the varied expressions of the social subject. Since the years 1930 the social worker acts in the area of the Education, with an originating from knowledge the human and social areas that you/he/she makes possible him/it to contribute, undisciplinement, close to the pedagogic team of the School Education. The clarity of the you know and of the necessary competences to intervene in that field of specific work makes possible the legitimation of the identity, of the social worker professionalization and the formalization of his/her practice. The Theory ends that the profissionality and the social worker professionalism is built and it is recognized in the area of the Education starting from the knowledge of the you know and pertinent competences to intervene in that context, beginning that knowledge on the part of the category of the Social Service and of the formation organs and representation of the profession so that the school community - administration and pedagogic coordination, teachers and students - he understands and recognize the social worker necessary intervention in that field. The formalization of those you know and competences are built starting from actions and thought mobilizations and operation in the group of the category, and not for isolated actions and individualized. It is revealed, in the opinion of the ones that represent Regional Council of Social Service, a wide vision of the social worker in that space exercising, among other, functions that don't compete to the professional's profile or restricted to actions and techniques historically exercised in their work fields. A new profile of the professional of the Social Service that it acts in the School Education is possible when his/her action is visualized centered not just in the work with the family, but, doing of the school a proposition space and execution of programs, projects, studies and social researches. He intends, an action politics and of popularization on them know and the social worker competences in the School Education